Cardiovascular disease in patients with osteogenesis imperfecta — a nationwide, register-based cohort study. (15th December 2016) - Folkestad, Lars; Hald, Jannie Dahl; Gram, Jeppe; Langdahl, Bente L.; Hermann, Anne Pernille; Diederichsen, Axel CP; Abrahamsen, Bo; Brixen, Kim
Abstract: Background: Osteogenesis imperfecta (OI) is a hereditary connective tissue disease often due to mutations in genes coding for type 1 collagen. Collagen type 1 is important in the development of the heart and vasculature. Little is known about the risk of cardiovascular disease (CVD) in OI. Objective: To investigate the risk of symptomatic CVD in OI. Design: A Danish nationwide, population-based and register-based longitudinal open cohort study. Participants: All patients registered with the diagnosis of OI from 1977 to 2013 and a reference population matched 5:1 to the OI cohort. Measurements: Sub-hazard ratios for mitral and aortic valve regurgitation, atrial fibrillation and flutter, heart failure and vascular aneurisms and dissections comparing the OI cohort to the reference population. Results: We identified 687 cases with OI (379 women) and included 3435 reference persons (1895 women). The SHR was 6.3 [95% CI: 2.5–15.5] for mitral valve regurgitation, 4.5 [95% CI: 1.4–13.9] for aortic valve regurgitation, 1.7 [95% CI: 1.1–2.8] for atrial fibrillation/flutter, and 2.3 [95% CI: 1.4–3.7] for heart failure. The SHRs were not increased arterial aneurisms or dissections. Limitation: Our results were limited by lacking clinical information about phenotype and genotype of the included patients. Conclusion: We confirm that patients with OI have an increased risk of CVD compared to the general population. This held true even when adjusting for factors that are known to contribute to development of these diseases. Our results suggest that the collagenopathy seen in OI may be part of the pathogenesis of CVD in OI. Highlights: Osteogenesis imperfecta (OI) is a hereditary disease of connective tissue. Patients have increased risk of heart failure. Patients have increased risk of atrial fibrillation or flutter. Patients have increased risk of aortic and mitral valvulopathies. Adult patients with OI could benefit from regular ECG and echocardiography.